2020
DOI: 10.1017/s0007114520002664
|View full text |Cite
|
Sign up to set email alerts
|

Validation and calibration of the Eating Assessment in Toddlers FFQ (EAT FFQ) for children, used in the Growing Up Milk – Lite (GUMLi) randomised controlled trial

Abstract: The Eating Assessment in Toddlers FFQ (EAT FFQ) has been shown to have good reliability and comparative validity for ranking nutrient intakes in young children. With the addition of food items (n 4), we aimed to re-assess the validity of the EAT FFQ and estimate calibration factors in a sub-sample of children (n 97) participating in the Growing Up Milk – Lite (GUMLi) randomised control trial (2015–2017). Participants completed the ninety-nine-item GUMLi EAT FFQ and record-assisted 24-h recalls (24HR) on two oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Pearson correlation coefficients ranging from 0.5 to 0.7 indicate a good correlation, while those larger than 0.7 indicate a very strong correlation between the two methods [ 42 ]. At the nutrient level, for most parameters, the correlations between the two methods ranged from being good to very strong.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson correlation coefficients ranging from 0.5 to 0.7 indicate a good correlation, while those larger than 0.7 indicate a very strong correlation between the two methods [ 42 ]. At the nutrient level, for most parameters, the correlations between the two methods ranged from being good to very strong.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson correlation coefficients ranging from 0.5 to 0.7 reflected a good correlation while coefficients larger than 0.7 showed a very strong correlation between the two assessment methods [ 25 ]. From our results, the correlations between the two assessment methods were good to very strong for most parameters, except for iron, manganese, and sodium, for which only acceptable correlations were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials have been conducted in the last years regarding YCF consumption. An early development of overweight and obesity and higher concentrations of IGF-1 at 2.5 years of age have been associated with an excessive amount of protein intake [35], and some studies [19,60,62,64] have shown that children who consumed YCF had a lower protein intake than those who consumed cow's milk. Moreover, results showed that toddlers who consumed YCF with a lower protein content than cow's milk had a lower percentage of body fat mass [60,62], and that IGF-1 concentration at 2 years was positively associated with the total cow's milk intake [68].…”
Section: Discussionmentioning
confidence: 99%
“…In the GUMLi study, authors validated the Eating Assessment in Toddlers FFQ (EAT FFQ) [64], that estimate the content of protein, total fat, carbohydrate, fiber, Ca, Fe, Zn, and Vitamins B12, C, and D. Subsequently they administered the EAT FFQ [19], which describe dietary intake over previous 4 weeks at 3, 6, 9, and 12 months of the intervention.…”
Section: Which Milk Is the Best Choice During The Second Year Of Life? Evidence From Clinical Trialsmentioning
confidence: 99%